2011
DOI: 10.4061/2011/404969
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Osteoporosis Care Gap in Hip Fracture Patients: An Opportunity to Decrease Recurrent Fractures and Hospital Admissions

Abstract: Background. Falls and hip fractures are an increasing health threat to older people who often never return to independent living. This study examines the management of bone health in an acute care setting following a hip fracture in patients over age 65. Methods. Retrospective chart review of all patients admitted to a tertiary health facility who suffered a recent hip fracture. Results. 420 charts of patients admitted over the course of a year (May 1, 2007–April 31, 2008) were reviewed. Thirty-seven percent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In our study of patients involved in FTOP, among patients with no previous osteoporosis treatment 50% had osteoporosis treatment initiated by 6 months post discharge. These rates are consistent with previous studies of case manager osteoporosis programs [ 15 , 20 , 21 ]. For example, a randomized controlled trial evaluating a case manager osteoporosis program in acute care for hip fracture patients demonstrated improved rates of osteoporosis treatment in patients involved in the program, with treatment initiated in 51% of these patients [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…In our study of patients involved in FTOP, among patients with no previous osteoporosis treatment 50% had osteoporosis treatment initiated by 6 months post discharge. These rates are consistent with previous studies of case manager osteoporosis programs [ 15 , 20 , 21 ]. For example, a randomized controlled trial evaluating a case manager osteoporosis program in acute care for hip fracture patients demonstrated improved rates of osteoporosis treatment in patients involved in the program, with treatment initiated in 51% of these patients [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…21 Using various types of intervention programs has demonstrated success, with the end goal of improving osteoporosis follow-up in high-risk patients. 1,2,4,7,8,[12][13][14][15][16][17][18][19] Our study builds on this current trend. However, most of these programs would be difficult to implement at an average hospital system, given the lack of standardization and automation.…”
Section: Discussionmentioning
confidence: 92%
“…1,2,4,[7][8][9][11][12][13][14][15][16][17][18][19][20] Despite this burden, current literature demonstrates the low rate of follow-up care received by patients experiencing fragility fractures. 1,2,4,7,8,[12][13][14][15][16][17][18][19] We chose our patient population based on recommendations from the National Osteoporosis Foundation, which states that all individuals 50 years of age experiencing fragility fractures should be evaluated and treated for osteoporosis. 21 Using various types of intervention programs has demonstrated success, with the end goal of improving osteoporosis follow-up in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…When fractures require acute treatment, admission to hospital provides clinicians with the opportunity to initiate osteoporosis screening and deliver interventions to modify the risk of subsequent fractures. [6][7][8] Efficacious treatments are available to reduce the risk of repeat fracture, including anti-resorptive medicines such as bisphosphonates (risedronate, alendronate and zoledronic acid) and denosumab along with anabolic agents like teriparatide. [9][10][11][12] However, significant treatment gaps exist: international reviews have demonstrated that less than 25% of patients with MTF receive appropriate screening, diagnosis and treatment, 13,14 with the same demonstrated locally some 15 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore vital to consider future fracture risk and secondary prevention at the time of initial MTF presentation. When fractures require acute treatment, admission to hospital provides clinicians with the opportunity to initiate osteoporosis screening and deliver interventions to modify the risk of subsequent fractures 6–8 …”
Section: Introductionmentioning
confidence: 99%